2019
DOI: 10.3390/ani9030102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Garlic Powder on Growth Performance, Rumen Fermentation, and the Health Status of Lambs Infected by Gastrointestinal Nematodes

Abstract: For the study, forty lambs were weighed and assigned into two treatments to determine the effects of feeding garlic powder on growth performance, rumen fermentation, and the health status of lambs infected with gastrointestinal nematodes (GINs). The lambs were fed with a basal diet without or with 50 g/kg garlic powder for 84 d. Data were analyzed by a general linear or mixed model of SAS software and differences were considered statistically significant if p ≤ 0.05. Results showed that garlic powder supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 43 publications
6
34
1
Order By: Relevance
“…Recent ndings showed that the garlic (for example garlic powder), garlic extracts (for example garlic oil) and garlic by-products (for example garlic husk and garlic leaf) had potential to modify rumen fermentation, improve animal performance, and might be an alternative for growth promoting feed antibiotics [16][17][18]. In the present study, an increase of ADG was observed in the GAS group compared with that in the control group, which is consistent with previous study [18].…”
Section: Discussionsupporting
confidence: 92%
“…Recent ndings showed that the garlic (for example garlic powder), garlic extracts (for example garlic oil) and garlic by-products (for example garlic husk and garlic leaf) had potential to modify rumen fermentation, improve animal performance, and might be an alternative for growth promoting feed antibiotics [16][17][18]. In the present study, an increase of ADG was observed in the GAS group compared with that in the control group, which is consistent with previous study [18].…”
Section: Discussionsupporting
confidence: 92%
“…Sixteen healthy Ujumqin lambs with a mean ± SD live weight of 31.9 ± 4.3 kg were selected and individually weighed. Prior to the formal feeding experiment, all lambs were dewormed with a combination of abamectin, albendazole and levamisole (0.2, 5.0 and 7.5 mg/kg BW, respectively) to eliminate existing GINs, with no fecal eggs subsequently identified with the McMaster technique [ 2 ]. At 28 days after deworming, all lambs were artificially orally drenched with 3rd stage larvae of mixed nematodes (0.89 ± 0.04 Haemonchus contortus , 0.08 ± 0.04 Ostertagia circumcincta and some other species of nematodes, as assessed by light microscopy) only once, which were prepared by the egg hatching procedure as described by Zhong et al [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nearly all grazing animals on pasture-based systems are exposed to helminths. Gastrointestinal nematode (GINs) infection is a major factor limiting profitability for grazing sheep [ 2 ]. In addition to direct adverse effects on growth performance and health, GINs infection also indirectly reduces meat quality, including changed fatty acid composition and flavor of muscle, lighter meat color, increased tenderness, causing poor conformation of sheep carcasses, increased meat fattiness, decreased polyunsaturated fatty acid content and lighter meat color [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The restriction is due to the concerns over the spread of resistant pathological bacteria and the residues of antibiotics in animal products [1,2]. This has raised the interest in alternative phytogenic feed additives to improve livestock health and production [3,4]. One potential option is the use of licorice ( Glycyrrhiza uralensis ) root extract as a feed additive, which has been investigated mainly in monogastrics over the last 15 years [5,6,7] and scarcely in ruminants.…”
Section: Introductionmentioning
confidence: 99%